2013
DOI: 10.4028/www.scientific.net/amr.802.169
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free Cu-Si-Zn Brass with Tin Addition

Abstract: In this work, lead-free silicon brass (Cu-Si-Zn) with tin addition was studied to investigate on the comparative influence of the adding and non-adding tin on the microstructures and microhardness. In order to produce new alloy compositions, varied amount of silicon (0.5, 1.0, 2.0, 3.0 wt%) were incorporated. The ranges of chemical compositions were copper contents between 58.7 and 60.3 wt%, tin content 0.6 wt% and zinc remaining. The silicon brasses were prepared by melting pure elements with a graphite cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…It was also noted that tin was dissolved in the solid solution beta phase more than that in the alpha phase, which was in accordance with the previous research. 7) While bismuth was insoluble in the brass alloy and formed only pure bismuth particles as shown in this study. It was noted that the microstructures observed in the present work were different from a traditional CuZnBi alloy microstructure as shown schematically in Fig.…”
Section: Microstructures and Chemical Analysissupporting
confidence: 50%
“…It was also noted that tin was dissolved in the solid solution beta phase more than that in the alpha phase, which was in accordance with the previous research. 7) While bismuth was insoluble in the brass alloy and formed only pure bismuth particles as shown in this study. It was noted that the microstructures observed in the present work were different from a traditional CuZnBi alloy microstructure as shown schematically in Fig.…”
Section: Microstructures and Chemical Analysissupporting
confidence: 50%
“…The addition of Sn to the brass alloy promoted the formation of β -and G-phases. Previous research showed that the hardness of the G-phase is more than that of β ', which in turn is harder than the α-phase [8,17,33]. Therefore, the formation of these phases caused the hardness of the Cu-30 wt-% Zn brass to increase.…”
Section: Grain Size and Hardnessmentioning
confidence: 97%
“…Bi also segregates to the grain boundaries, which causes the brittleness of the casting part to increase [5][6][7]. Si, which expands the stability of hard phases in the microstructure and hence enhances machinability, is another substitute for Pb in brass alloys [8]. However, an increase in the rate of tool wear, which increases the cost of machining, is a significant disadvantage of this element [9].…”
Section: Introductionmentioning
confidence: 99%
“…The combined addition of phosphorus and magnesium has proved effective in improving the electrical conductivity of Cu-1.5Ni-0.3Si alloys [24]. Puathawee et al [32] recorded an average hardness of 123.4 HV for Cu-2Si alloy via the addition of 39.5wt% Zn. Li et al [16] and Wang et al [22] developed Cu-Ni-Si-Cr-Zr alloys of average hardness (197 HV) and electrical conductivity (32.7%IACS).…”
Section: Introductionmentioning
confidence: 99%